Audit and Control of Distributed Data Processing Systems (Book). - Hooks, Karen L.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Abstract Reviews the book "Audit and Control of Distributed Data Processing Systems," by Larry J. Duff.